The Effects of Online Small Group Discussion on Students’ Reading Comprehension - Muhammad Ihzan Ihzan; Nurdin Noni; Muhammad Basri Jafar (Tamaddun Life, 2022)
The present study aims to examine two cases, namely: (1) the effect of online small group discussion on students' reading comprehension, and (2) students' perception of the effect of online small group discussion on students' reading comprehension. The purpose of this study was to determine the effect of online small group discussion on students' reading comprehension, to determine students' perceptions of the effect of online small group discussion on students' reading comprehension. Implementing learning to understand English reading. This research employed quantitative approach. In this study, the authors used purposive sampling to collect the data. This study was attended by 30 participants and was conducted at the English Department of the Indonesian Muslim University, Makassar. The results of this study indicated that the use of Small Group Discussion method in learning English reading comprehension in the network was quite effective in developing students' reading comprehension. It was observed that the learning process was done through online applications such as Zoom and Whatsapp. Overall, these results can be a reflection for teachers and students to be even more active in learning to understand English writing or scripts particularly in an online environment.